Estimation of ecological adaptability and stability of promising winter barley varieties and lines in the competitive variety testing - E. G. Filippov; А. А. Dontsova; D. Р. Dontsov; I. М. Zasypkina (Зерновое хозяйство России, 2021)
Plant breeding plays an important role in increasing grain production and improving its quality. Currently, the de[1]velopment of new ecologically adaptable varieties that can more effectively use the climatic and soil resources of the regions is of great importance. The purpose of the current study was to analyze the parameters of ecological adapt[1]ability and stability of varieties and lines of the competitive variety testing (2018–2020) in the Rostov region. There have been studied five winter barley varieties ‘Timofey’, ‘Erema’, ‘Vivat’, ‘Marusya’, ‘Foks 1’ and six winter barley lines ‘Pallidum 1899’, ‘Pallidum 1972’, ‘Parallelum 1976’, ‘Parallelum 1979’, ‘Parallelum 1980’, ‘Parallelum 1981’ developed by the FSBSI “ARC “Donskoy”. The sowing was carried out with a Wintersteiger Plotseed seeder, accounting plots area was 10 m². The forecrop was peas. The placement was systematic; the number of repetitions was 6. The factor ‘year’ had the greatest influence on the formation of productivity with 97.07%. The analysis of environmental condi[1]tions showed that there were more favorable growing conditions in 2018 (Ij = +1.27), and unfavorable ones in 2019 (Ij = -1.62). The productivity of the varieties ‘Erema’ (9.4 t / ha; +0.7), ‘Marusya’ (9.7 t / ha; +1.0) and the line ‘Pallidum 1972’ (9.4 t / ha; +0.7) exceeded that of the standard variety. There has been established the varieties and lines ‘Timofey’, ‘Pallidum 1972’, ‘Parallium 1979’, ‘Parallum 1981’ had increased stress resistance. The varieties ‘Erema’, ‘Marusya’ and the line ‘Pallidum 1972’ had a higher compensatory ability. According to the analysis of adaptability, the varieties ‘Erema’, ‘Marusya’, ‘Foks 1’, as well as the line ‘Parallelum 1976’ were identified as responsive with linear regression coefficient values above one. The lines ‘Pallidum 1972’, ‘Parallelum 1979’, ‘Parallelum 1981’ and the variety ‘Marusya’ consistently produced high yields. The lines ‘Pallidum 1972’, ‘Parallum 1979’ and ‘Parallum 1981’ possessed high stability index (L) and PUSS index.